Start Your Own eBay Business - Spencer, Christopher Matthew (Entrepreneur Press, 2020)
eBay is empowering small businesses everywhere by offering ecommerce and marketing tools to reach customers around the globe. With more than 170 million buyers in 190 markets globally, eBay makes it easy for you to start, run, and grow a new or existing business wherever you are
Description based on publisher supplied metadata and other sources